2023
DOI: 10.3390/ph16060821
|View full text |Cite
|
Sign up to set email alerts
|

Laponite-Based Nanocomposite Hydrogels for Drug Delivery Applications

Abstract: Hydrogels are widely used for therapeutic delivery applications due to their biocompatibility, biodegradability, and ability to control release kinetics by tuning swelling and mechanical properties. However, their clinical utility is hampered by unfavorable pharmacokinetic properties, including high initial burst release and difficulty in achieving prolonged release, especially for small molecules (<500 Da). The incorporation of nanomaterials within hydrogels has emerged as viable option as a method to trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“…These excellent characteristics are derived from the intrinsic properties of LAP and gelatin. Laponite nanoplatelets are non-cytotoxic both in vivo and in vitro 48 , and in 20–50 days, they can naturally dissociate into osteogenesis-related ions (Li + , Mg 2+ , and silicates) in physiological environments 49 . It has been extensively reported that gelatin is highly biocompatible and biodegradable without toxicity and immunogenicity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…These excellent characteristics are derived from the intrinsic properties of LAP and gelatin. Laponite nanoplatelets are non-cytotoxic both in vivo and in vitro 48 , and in 20–50 days, they can naturally dissociate into osteogenesis-related ions (Li + , Mg 2+ , and silicates) in physiological environments 49 . It has been extensively reported that gelatin is highly biocompatible and biodegradable without toxicity and immunogenicity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The entire release system was kept in a shaker at 37 °C and 100 rpm speed, and the sink condition was guaranteed during the test process. At the predetermined time intervals (1,3,12,24,48,72,96,120,144,168,192,216, and 240 h), 5 mL of dissolution medium was taken out, and an equivalent volume of fresh medium was added. To ensure the smooth dissolution of IND drugs, 50 mL of release media was renewed every 2 days.…”
Section: Acs Applied Polymer Materialsmentioning
confidence: 99%
“…Such a phenomenon would bring about short efficacy time for treatment and excessive drug absorption into the blood over the toxic dose. Moreover, hydrogel preparations often need freeze-drying or cold preservation to prevent polymer chains from hydrolysis. …”
Section: Introductionmentioning
confidence: 99%
“…Smaller particle-sized substances exhibit enhanced cartilage penetration and cellular uptake, which are key for targeted therapy in OA [80]. Hydrogels can specifically target cartilage and directly deliver bioactive factors to lesion sites, including antioxidants, anti-inflammatory agents, and growth factors targeting chondrocytes [81][82][83]. Li et al validated that intra-articular injections of biofactors directly to inflamed sites in an OA animal model promoted cartilage repair when combined with hydrogels [29].…”
Section: Target Transmissionmentioning
confidence: 99%
“…The effects of drugs on cartilage and chondrocytes in OA are limited. Medications commonly used for OA include nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, analgesics, and immunosuppressants [82][83][84][85][86][87][88][89][90]. For instance, the sustained release of dexamethasone, with anti-inflammatory and immunosuppressive properties, by a hydrogel carrier enhances cartilage quality, alleviates arthritis symptoms, and promotes cartilage repair.…”
Section: Medicationmentioning
confidence: 99%